O conceito de TDAF: concepções e práticas de profissionais da saúde e educação - Camilo, Lujani Aparecida [UNESP] (2014)
A learning disability associated with hyperactive behavior has been one of the main complaints in outpatient clinics children's mental health. Among these complaints have that in Brazil related to Attention Deficit Disorder with or without Hyperactivity (ADHD). ADHD is associated with functional impairment in several areas (academic, professional, social), the causes of this disorder, although much researched and attributed to a combination of genetic, biological and environmental factors have not been fully elucidated, hampering the adoption of preventive strategies. Thus, in recent years, much has been heard of ADHD, and being the school environment which this most evident, this research seeks to understand how fundamentally conceived the concept of disease and disorder by health professionals and education. Objectives - The main objective of this research is to investigate the multidisciplinary team of the pediatric clinic of the Faculty of Medicine of Botucatu, and public school teachers in the same city that has sent children to the clinic, which their conceptions and practices about ADHD. Methodology - The research is qualitative, which technique is the collective subject discourse to analyze the data collected in this research because it gives voice to individuals and is suitable for treating qualitative data. Results - The concepts of both health and education groups, with respect to the predominant model in their speech, it was revealed that the hegemonic biomedical model is still present. With regard to health professionals, one realizes that these ties to hold the school, however, is not the true intersectionality between these institutions. In general, teachers, and health professionals, realize the exchange and discussion at a time after diagnosis in the public health system and education is flawed. Conclusion - There is need for a sectorial, which aims to find similarities between the concepts, principles and values ...